2007
DOI: 10.1152/ajpgi.00154.2007
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal preconditioning prevents inflammatory response by modulating heme oxygenase-1 expression in endotoxic shock model

Abstract: Gut mucosal injury observed during ischemia-reperfusion is believed to trigger a systemic inflammatory response leading to multiple organ failure. It should be interesting to demonstrate this relationship between gut and multiple organ failure in a sepsis model. Intestinal preconditioning (PC) can be used as a tool to assess the effect of intestinal ischemia in inflammatory response after LPS challenge. The aim of this study was to investigate the protective effect of PC against LPS-induced systemic inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The effects are associated with down-regulation of key steps leading to cell death and systemic inflammatory responses [10,15-17]. Indeed, intestinal ischemic preconditioning prevented inflammatory responses by modulating intestinal HO-1 expression in endotoxic shock model [18]. Furthermore, Wen et al [19] reported upregulation of HO-1 by chemical inducers prevented lipopolysaccharide (LPS)-induced acute hepatic injury.…”
Section: Introductionmentioning
confidence: 99%
“…The effects are associated with down-regulation of key steps leading to cell death and systemic inflammatory responses [10,15-17]. Indeed, intestinal ischemic preconditioning prevented inflammatory responses by modulating intestinal HO-1 expression in endotoxic shock model [18]. Furthermore, Wen et al [19] reported upregulation of HO-1 by chemical inducers prevented lipopolysaccharide (LPS)-induced acute hepatic injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of limb IP on sepsis-induced tissue injury has not yet been extensively studied. In only one study, the inflammatory response was shown to be modulated by intestinal IP in an endotoxemic shock model (28). …”
Section: Introductionmentioning
confidence: 99%
“…5 and 6) clearly demonstrated a major role of microsomal P450 enzymes in the protection of colon against inflammatory injury, our data do not exclude possible involvement of additional mechanisms or pathways, such as intestinal HO activity. Intestinal HO-1 expression was induced by intestinal inflammation in animal models, and increased HO-1 expression was found in colon biopsy from IBD patients (Otterbein et al, 1995;Willis et al, 1996;Paul et al, 2005;Tamion et al, 2007). Preinduction of HO-1 by cobalt protoporphyrin reduced extent of DSS-induced colitis in mice (Paul et al, 2005).…”
Section: Discussionmentioning
confidence: 99%